The Philippine Islands, 1493-1898 explorations by early navigators, descriptions of the islands and their peoples, their history and records of the Catholic missions, as related in contemporaneous books and manuscripts, showing the political, economic, commercial and religious conditions of those islands from their earliest relations with European nations to the close of the nineteenth century, Volume 52, 1841-1898. - Blair, Emma Helen d.1911., ed; Robertson, James Alexander 1873-1939; Bourne, Edward Gaylord 1860-1908 (The A.H. Clark Company, 1907)
In this final documentary volume of our series we present matter which is planned to bring out the salient points of the highly important period from 1841 to 1898, a little more than the last half-century of the Spanish regime, together with such bibliographical aids as will enable students to find readily the best and most available sources for the history of that time. The first two documents (written respectively by a civil official and a military commander) furnish a reliable and intelligent survey, by eyewitnesses, of political, economic, and social conditions in the islands in 1842-43; and thus supplement the similar relations (in vol. LI) dated fifteen years earlier.